Focal Adjustment for Star Tracker - Hai-bo, Liu; Yang, Jian-kun; Tan, Ji-chun; Su, De-zhi; Wang, Wen-liang; Li, Xiu-jian; Jia, Hui (Defence Science Journal, 2010)
Technique of measuring intensity distribution and size of spot image developed has been discussed, which is especially suitable for defocus adjustment in ground test of star tracker. A novel approach for choosing a proper defocusing position has been proposed based on collimator, Gaussian surface fitting method, and other ordinary instruments. It proves to be practical and adequate in the development of distant object tracking such as star tracker. Defence Science Journal, 2010, 60(6), pp.678-682, DOI:http://dx.doi.org/10.14429/dsj.60.36